Asymptotic behavior of Lebesgue functions of two variables - Kuznetsovci, O. I. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We describe the asymptotic behavior of Lebesgue functions generated by the rhombic partial Fourier sums.